Industry perspective on journalism education curriculum in Malaysia - Yusof, Norhafezah; Ismail, Awan; Ismail, Rizalawati; Aripin, Norizah; Kasim, Azahar; Ishak, Mohd Sobhi (Universiti Utara Malaysia Press, 2018)
Purpose - This study investigated media and communication practitioners’ perspectives on the journalism education curriculum in Malaysia. Curriculum plays an important role in providing quality education for students. Journalism is a dynamic field that integrates industrial experience and fundamental knowledge in the field from higher educational institutions. Scholars in the field are divided on the issue of whether it is important for academia to consider input from industrial players in shaping the curriculum on journalism education in higher institutions of learning. Methodology - Drawing from the researchers’ experiences and guidelines from the Malaysian Qualifications Agency, the Taba Model was adapted as the theoretical framework for the study. The study used a semi-structured interview method. Fifteen experts were interviewed. They have served more than 10 years in the media industry and have held various executive positions. The interview protocol was developed based on the literature review and guidelines from the curriculum review of Communication and Media Studies. The interviews were conducted at the offices or homes of interviewees. Each interview ranged from 1 to 2 hours. The data was analysed using thematic analysis. Findings - The findings revealed four main themes, namely 1) Strong general knowledge requirement, 2) the right skills matter, 3) Received: 13 December 2017 Accepted: 1 May 2018 150 Malaysian Journal of Learning and Instruction: Vol. 15 (No. 1) June 2018: 149-172 Interest in the field – ability to adapt and learn, and 4) Specialised knowledge. The analysis of interviews indicated that curriculum needs to be revised based on academic convention and industrial needs. Significance - These findings lend further support to the clarion call for industry and academia to collaborate extensively in nurturing high quality graduates in journalism. Keywords: Communication and media, curriculum, industry, graduates, model.